PERSEPSI MAHASISWA TERHADAP MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATA KULIAH ENGLISH FOR SPECIFIC PURPOSE - Ray Suryadi; Alifiah Pratiwi; Rahedin Suwo; Syamsinar (EPIGRAM (e-journal), 2023)
One technology that is currently gaining traction is Augmented Reality (AR). Augmented Reality (AR) is a technology used to combine the virtual world and the real world, this system is closer to the real environment, so that the boundary between them becomes thin. Augmented Reality serves the purpose of developing new technology that allows for real-time interaction. This technology allows users to view 3D objects in real time by using a smartphone. Based on observations and feedback from students during the process of learning English at a private school, students believe that the education they receive is inadequate because it is solely based on text/modules. Teaching modules often used are only material summaries, besides that the availability of authentic materials is very limited. As a result of this, a new interactive learning medium based on Augmented Reality has been developed to teach and learn English in the ESP curriculum for Jasmani students. The goal of this research is to learn about students’ perceptions of Phisyc Education toward Augmented Reality-based learning media in English. According to the findings of the study, 93% of the population is interested in using Augmented Reality applications, and this include in category as very agree.